Transparency of Public Information by Kertasari Village, Ciamis District, Ciamis Regency - Risyaldi Rahmattulloh; Arie Budiawan; Fachmi Syam Arifin (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to describe the implementation of Public Information Transparency by Kertasari Village, Ciamis District, Ciamis Regency, in improving good governance. This research was motivated by the suboptimal implementation of public information disclosure, as indicated by limited access to information, inadequate utilization of communication media, and low community participation in monitoring public information. The study employed a qualitative descriptive methodology, with data collected through observation, interviews, and documentation. The focus of the research consisted of four aspects: (1) information accessibility, (2) accountability, (3) community participation, and (4) communication effectiveness in the dissemination of public information. However, several challenges were identified, including limited technological infrastructure, low human resource capacity, and the lack of effective integration of information communication media. The results of the study indicate that the implementation of Public Information Transparency by Kertasari Village, Ciamis District, Ciamis Regency, has not yet been carried out optimally. Enhancing public information transparency requires strengthening facilities and infrastructure, improving the competence of government personnel, and optimizing information systems and communication media. These efforts are expected to improve access to information, increase community participation, and enhance accountability in local government administration at the village level. Keywords: Transparency, Public Information, Public Service, Community Participation.